1992
DOI: 10.1007/bf00194465
|View full text |Cite
|
Sign up to set email alerts
|

Cluster theory for water sorption in wood

Abstract: A review of water interaction in cellulosic-systems, particularly wood, is presented.Discussed are the different states of water in these systems according to Nuclear Magnetic Resonance results, the BET, Dent, and Hailwood and Horrobin sorption isotherm models. The discussion includes details of water structure, and, conformational analysis of cellulose crystals and amorphous cellulose. The water cluster theory is used to more adequately explain the sigrnoid curve of the wood isotherm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 38 publications
3
55
0
4
Order By: Relevance
“…The reorganization of the wood ultrastructure in relation to sorption processes was also reported by Bonarski and Olek (2006). Additionally, Hartley et al (1991) suggested that during sorption processes not only wood components changed the ultrastructure but also bound water molecules might form water clusters. In Eq.…”
Section: Mathematical Modelsupporting
confidence: 58%
“…The reorganization of the wood ultrastructure in relation to sorption processes was also reported by Bonarski and Olek (2006). Additionally, Hartley et al (1991) suggested that during sorption processes not only wood components changed the ultrastructure but also bound water molecules might form water clusters. In Eq.…”
Section: Mathematical Modelsupporting
confidence: 58%
“…Freezing bound water exhibits a phase change between -10 and -20°C, whereas non-freezing bound water does not freeze down to -70°C (Berthold et al 1996). Freezing bound water has therefore been assumed to be less confined by and more loosely bound to the cell wall than non-freezing bound water, for example, as water clusters in line with theoretical considerations of Hartley et al (1992) and Hartley and Avramidis (1993). However, Berthold et al (1996) only found freezing bound water in ligno-cellulosic model compounds containing weak or strong acidic groups, that is, not in native wood.…”
Section: Green Wood and Fibre Saturationmentioning
confidence: 96%
“…BET model theory proposes a multilayer adsorption, a monolayer strongly attached to the chains of the material, and the subsequent layers thermodynamically tend to behave in the same way, however, different from the monolayer and with similar characteristics of liquid water (Hartley et al, 1992). The applicability of the BET model is limited to the low range of a w (0-0.75).…”
Section: Modeling Of Experimental Datamentioning
confidence: 99%